Analysis of Factors Influencing Transfer Pricing: Analisis Faktor-Faktor yang Mempengaruhi Harga Transfer - Evi, Tiolina; Septo , Ign; Sasongko, Fajar (Universitas Muhammadiyah Sidoarjo, 2023)
Transfer pricing can be a problem as well as an opportunity for companies to get high profits. Global transfer pricing also aims to control the flow of resources between divisions and motivate businesses. The purpose of this study is to analyze the effect of the tax burden, company size and foreign ownership on transfer pricing. This research is a quantitative research.. The sample technique used in this research is purposive sampling. The samples used were sixteen manufacturing companies. The data used in this study were obtained from the annual financial reports of manufacturing companies for 2016-2018. The analysis technique used in this study was multiple linear regression which was processed using the SPSS version 25 application. The results of this study found that simultaneously the tax burden, company size and foreign ownership have a significant effect on transfer pricing. Partially, this study shows that tax burden has no significant effect on transfer pricing, company size has a significant effect on transfer pricing, and foreign ownership has no significant effect on transfer pricing. Companies must carry out transparent transfer pricing reporting, including compiling separate transfer pricing reports in accordance with tax requirements in various countries. Transparent reporting will support the company's integrity and accountability in carrying out transfer pricing practices.